PENGETAHUAN DENGAN PREVENTION MASYARAKAT DALAM MENGHADAPI BENCANA BANJIR DI DESA TOLITE KECAMATAN BOLIYOHUTO - Pipin Yunus; Arifin Umar; Rifki Maulana (Universitas Muhammadiyah Gorontalo, 2019)
Disaster is the incident or sequence which threatens and disrupts people’s lives that caused of natural and non natural factors as well as human factors resulting in fatalities environmental damage, property loss and psychological impact. The objective was to determine relationship between knowledge with society’s preventions in facing flood disasters at Tolite village, Boliyohuto sub district. The design used quantitative descriptive, a method based on the philosophy of positivism. The populations used cross sectional study with sampling used slovin formula thus obtained samples are 92 respondents. Statistical test used chi-square. The significance value was p-value = 0,000 small than (p= <0,05) therefore Ho is rejected and Ha is accepted. Concluded, there is significant relationship between knowledge with society’s preventions in facing flood disasters at Tolite village, Boliyohuto sub district.